2004
DOI: 10.1051/0004-6361:20035676
|View full text |Cite
|
Sign up to set email alerts
|

A new sample of large angular size radio galaxies

Abstract: Abstract. We present in this paper a detailed study of a new sample of large angular size FR I and FR II radio galaxies and compare the properties of the two classes. As expected, a pure morphology based distinction of FR Is and FR IIs corresponds to a break in total radio power. The radio cores in FR Is are also weaker than in FR IIs, although there is not a well defined break power. We find that asymmetry in the structure of the sample members must be the consequence of anisotropies in the medium where the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Morganti et al 1993). Similarly to Lara et al (2004), we derive this parameter using S core measured at 5 GHz and S total at 1.4 GHz.…”
Section: Radio Core Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Morganti et al 1993). Similarly to Lara et al (2004), we derive this parameter using S core measured at 5 GHz and S total at 1.4 GHz.…”
Section: Radio Core Propertiesmentioning
confidence: 99%
“…In the sample of Lara et al (2004) comprising of large size FRI and FRII-type sources, the authors found an excess of sources with a core power larger than expected from their total power, and considered whether the ratio of P core 5 and P core norm , i.e. that calculated from the relation of Giovannini et al (cf.…”
Section: The Core Prominence and The Orientation Indicatormentioning
confidence: 99%
“…In the complete sample of 3CR radio sources (Laing et al 1983) around 6% of the sources are giants; there are about 100 known. Giant radio galaxies typically have radio powers below 10 26.5 W Hz −1 sr −1 , have linear sizes less than 3 Mpc, and are observed at redshifts z < 0.25, even though z < 0.5 could be assumed as an upper limit (Ishwara-Chandra & Saikia 1999;Schoenmakers et al 2000;Lara et al 2004;Saripalli et al 2005;Machalski et al 2007). The P-D diagram (Lara et al 2004;Ishwara-Chandra & Saikia 1999) shows a dearth of high luminosity GRG, as predicted by evolutionary models (Blundell et al 1999;) and a maximum GRG linear size cut-off of 3 Mpc.…”
Section: Introductionmentioning
confidence: 99%
“…Giant radio galaxies typically have radio powers below 10 26.5 W Hz −1 sr −1 , have linear sizes less than 3 Mpc, and are observed at redshifts z < 0.25, even though z < 0.5 could be assumed as an upper limit (Ishwara-Chandra & Saikia 1999;Schoenmakers et al 2000;Lara et al 2004;Saripalli et al 2005;Machalski et al 2007). The P-D diagram (Lara et al 2004;Ishwara-Chandra & Saikia 1999) shows a dearth of high luminosity GRG, as predicted by evolutionary models (Blundell et al 1999;) and a maximum GRG linear size cut-off of 3 Mpc. An estimate of the predominant process of radiative losses, obtained by separating the contributions of the inverse Compton and synchrotron losses, shows that the ratio of the estimated B CMB /B eq increases with linear size, and IC losses dominate the radiative losses in GRG (Ishwara-Chandra & Saikia 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We are aware that for redshift values greater than ∼0.14 (for which the linear size of the S-shaped structure is larger than 1 Mpc), the radio luminosity at 1400 MHz (log L 1400 ∼25.6) falls in the region of transition between FRI and FRII-type large radio galaxies (see Lara et al 2004). …”
Section: Extragalactic Emission From G2937+01?mentioning
confidence: 99%